Two new species of Adapterops (Coleoptera: Anthribidae) from protected areas of northern Madagascar, with a key to species, and new faunistic data on the genus - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2017)
Two new species, Adapterops mamyi Trýzna & Baňař sp. nov. and A. dimbyi Trýzna & Baňař sp. nov. (Anthribidae: Choraginae: Araecerini), from northern Madagascar are described and illustrated. A key to the species of the genus Adapterops Frieser, 2010 is given. New and interesting faunistic records of the genus are provided. Male terminalia are described for the first time, tegminal process is reported as a unique feature within the family.
Keywords: brouci; Madagaskar; Coleoptera, Anthribidae, Choraginae, Adapterops, taxonomy, new species, male terminalia, tegminal process, key, faunistics, Madagascar; Madagascar; Animals; mužské pohlaví; Male; zvířata; Coleoptera